Spliced XBP1 Levels Determine Sensitivity of Multiple Myeloma Cells to Proteasome Inhibitor Bortezomib Independent of the Unfolded Protein Response Mediator GRP78 - Borjan, Bojana; Kern, Johann; Steiner, Normann; Gunsilius, Eberhard; Wolf, Dominik; Untergasser, Gerold (Frontiers in Oncology, 2020)
Background: Mechanisms mediating resistance against the proteasome inhibition by bortezomib (BTZ) in multiple myeloma (MM) cells are still unclear. We analyzed the activation of the unfolded protein response (UPR), induction of prosurvival, and apoptotic pathways after proteasome inhibition in BTZ-sensitive and -resistant cells. Thereafter, these findings from tissue culture were proofed on MM cells of BTZ-sensitive and BTZ-refractory patients. Methods: Proteasomal and ABC transporter activities were measured in sensitive and resistant cell lines by the use of the respective substrates. TP53 gene loss and mutations were determined by cytogenetics and targeted NGS. UPR pathways, proteasome subunit levels and protein secretion were studied by Western Blot analysis, and apoptosis was determined by flow cytometry. MM cell lines were stably transfected with inducible GRP78 expression to study unfolded protein expression. Transient knock-down of GRP78 was done by RNA interference. Splicing of XBP1 and expression of GRP78 was studied by real-time PCR in CD138-enriched MM primary cells of BTZ-refractory and -sensitive patients. Results: BTZ-sensitive cells displayed lower basal proteasomal activities. Similar activities of all three major ABC transporter proteins were detected in BTZ-sensitive and resistant cells. Sensitive cells showed deficiencies in triggering canonical prosurvival UPR provoked by endoplasmic reticulum (ER) stress induction. BTZ treatment did not increase unfolded protein levels or induced GRP78-mediated UPR. BTZ-resistant cells and BTZ-refractory patients exhibited lower sXBP1 levels. Apoptosis of BTZ-sensitive cells was correlating with induction of p53 and NOXA. Tumor cytogenetics and NGS analysis revealed more frequent TP53 deletions and mutations in BTZ-refractory MM patients. Conclusions: We identified low sXBP1 levels and TP53 abnormalities as factors correlating with bortezomib resistance in MM. Therefore, determination of sXBP1 levels and TP53 status prior to BTZ treatment in MM may be beneficial to predict BTZ resistance.